2023
DOI: 10.3390/nu15122713
|View full text |Cite
|
Sign up to set email alerts
|

Food Network Analysis in Non-Obese Patients with or without Steatosis

Abstract: Background: Steatosis is the most common liver disease worldwide and the leading cause of liver-associated morbidity and mortality. The aim of this study was to explore the differences in blood parameters and dietary habits in non-obese patients with and without steatosis. Methods: The present study included 987 participants with BMI < 30, assessed in the fourth recall of the MICOL study. Patients were divided by steatosis grade, and a validated food frequency questionnaire (FFQ) with 28 food groups was adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…For this reason, consuming a dish with mixed vegetables and eggs has a different effect on serum cholesterol concentrations than a low-fiber dish such as eggs and bacon. Mokhtari et al [26] used this argument to explain how consumption of more than four eggs per week was not significantly associated with the risk of SLD [43]. Our study population is linked to food traditions within the Mediterranean dietary pattern.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, consuming a dish with mixed vegetables and eggs has a different effect on serum cholesterol concentrations than a low-fiber dish such as eggs and bacon. Mokhtari et al [26] used this argument to explain how consumption of more than four eggs per week was not significantly associated with the risk of SLD [43]. Our study population is linked to food traditions within the Mediterranean dietary pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that a higher cholesterol consumption is associated with SLD and its exacerbation to NASH [35,36]. Baumgartner et al [26] has shown that daily egg consumption increases serum cholesterol and LDL-C concentrations in women [37] On the contrary, some randomized controlled trials observed that egg intake did not substantially change plasma TC, low-density lipoprotein cholesterol (LDL-C), HDL-C levels [38,39] or the TC/HDL-C ratio [39,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methodological details of this population-based study have been previously published [ 18 , 19 ]. For this study (called MICOL IV), recall of MICOL III patients was adopted [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate dietary habits, a validated food frequency questionnaire was administered during the visit, and each food (86 validated foods) was converted to mean daily intake in grams; the total was summarized in 28 food groups [ 20 ] established according to similarity type [ 24 ].…”
Section: Methodsmentioning
confidence: 99%